Brain calcification due to secondary hyperparathyroidism in a child with chronic renal failure - Bilge, Ilmay; Sadikoğlu, Banu; Emre, Sevinç; Sirin, Aydan; Tatli, Burak (The Turkish Journal of Pediatrics, 2005)
Secondary hyperparathyroidism (SHPT) has been better treated over the last decades, but the rate of metastatic calcifications, which were rarely seen before, was significantly increased in dialysis patients. The presence of uncontrolled SHPT, disorders of calcium (Ca) and phosphorus homeostasis and the common usage of large doses of vitamin D and Ca- containing phosphate binders may all contribute to the metastatic calcifications of soft tissues and vasculature leading to some life-threatening complications. Although the metastatic lung, heart, kidney, intestinal wall, skin, eye and soft tissue calcifications have been commonly reported in adults and also in children undergoing dialysis, the central nervous system calcification is a very rare condition. We report here a pediatric hemodialysis patient who presented with severe neurological findings due to the metastatic brain calcification secondary to his uncontrolled hyperparathyroidism.